2010
DOI: 10.1186/1742-2094-7-4
|View full text |Cite
|
Sign up to set email alerts
|

The Ca2+ activated SK3 channel is expressed in microglia in the rat striatum and contributes to microglia-mediated neurotoxicity in vitro

Abstract: BackgroundSmall-conductance Ca2+ activated K+ channels are expressed in the CNS, where KCNN2/SK2/KCa2.2 and KCNN3/SK3/KCa2.3 help shape the electrical activity of some neurons. The SK3 channel is considered a potential therapeutic target for diseases and disorders involving neuron hyper-excitability but little is known about its expression and roles in non-neuronal cells in either the healthy or damaged CNS. The purpose of this study was to examine expression of KCNN3/SK3 in CNS microglia in vivo and in vitro,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(73 citation statements)
references
References 79 publications
2
69
2
Order By: Relevance
“…We found that some ion channels in microglia contribute to their neurotoxic capacity, and identified roles of three K + channel types (K v 1.3, K Ca 2.3, K Ca 3.1) in production of nitric oxide, superoxide and peroxynitrite. [7][8][9] After acute CNS injury (e.g., stroke, trauma), the excitatory amino acid, glutamate, causes neuronal injury; thus, a crucial finding was that I Clswell channels in microglia are significantly permeable to glutamate (and . When the bath was perfused with the hypo-osmotic solution 5, the cell swelled (inset) and an outward-rectifying current activated, increased with time (vertical arrow) and reached a quasi-stationary plateau.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found that some ion channels in microglia contribute to their neurotoxic capacity, and identified roles of three K + channel types (K v 1.3, K Ca 2.3, K Ca 3.1) in production of nitric oxide, superoxide and peroxynitrite. [7][8][9] After acute CNS injury (e.g., stroke, trauma), the excitatory amino acid, glutamate, causes neuronal injury; thus, a crucial finding was that I Clswell channels in microglia are significantly permeable to glutamate (and . When the bath was perfused with the hypo-osmotic solution 5, the cell swelled (inset) and an outward-rectifying current activated, increased with time (vertical arrow) and reached a quasi-stationary plateau.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, after injury, microglia migrate to the site of injury, as shown in our recent studies of K + channels in rat models of optic nerve transection, ischemic stroke and intracerebral hemorrhage. [8][9][10] In addition, glutamate is involved in signaling between neurons, astrocytes and microglia; thus, potential outcomes of activating I Clswell include trans-activating NMDA receptors to evoke excitotoxic neuronal injury; 11 activating microglia through their metabotropic glutamate receptors, leading to production of other neurotoxic mediators; 12,13 and mediating glia-to-neuron signaling under inflammatory conditions. 14 Here, we first show that the biophysical and pharmacological properties of I Clswell in MLS-9 cells are as previously determined for primary rat microglia.…”
Section: Swelling Activated CL -Channels In Microgliamentioning
confidence: 99%
“…The messages for KCNN1/SK1, KCNN2/SK2, and KCNN3/SK3 channels were identified in rat cultured microglia; the KCNN3/SK3 showed predominant expression, which increased ϳ1.7 times following LPS stimulation (807). The immunoreactivity for KCNN3/ SK3 was found in microglial cells in healthy adult rat striatum; this immunoreactivity substantially increased after ischemic lesion (807). Finally, inhibition of KCNN3/ SK3 channels by 100 nM apamin or by 5 nM tamapin reduced microglial neurotoxicity and somewhat ameliorated microglial activation (807).…”
Section: Ca 2ϩ -Dependent Potassium Channelsmentioning
confidence: 97%
“…The K Ca channels are also involved in controlling the microglial respiratory burst; the treatment of microglial cells with apamin (selective blocker of KCNN2/SK2 channels) or with clotrimazole (KCNN4/SK4 channels inhibitors) markedly inhibited the respiratory burst (446). The messages for KCNN1/SK1, KCNN2/SK2, and KCNN3/SK3 channels were identified in rat cultured microglia; the KCNN3/SK3 showed predominant expression, which increased ϳ1.7 times following LPS stimulation (807). The immunoreactivity for KCNN3/ SK3 was found in microglial cells in healthy adult rat striatum; this immunoreactivity substantially increased after ischemic lesion (807).…”
Section: Ca 2ϩ -Dependent Potassium Channelsmentioning
confidence: 99%
“…In particular, it produces enhanced pain transmission in the spinal dorsal horn after spinal cord injury (Gwak & Hulsebosch, 2011). Recently, the SK3 ion channel has gained attention as a new therapeutic target for disorders involving neuron hyper-excitability (Schlichter et al, 2010). Results from the present study suggest direct interactions between Na-ASP-2 and extracellular SK3 peptides, thus raising the hope that this hookworm protein may hold promise as a new SK3 channel modulator with therapeutic potential.…”
Section: Potential Host Receptors Of Na-asp-2mentioning
confidence: 62%